CHEMICAL CHARACTERISTICS OF PEAT SOIL ON VARIOUS WATER TABLE DEPTHS IN DRAINAGE - Nurdiansyah, Nurdiansyah; Widiarso, Bambang; Gunawan, Joni (Fakultas Pertanian Universitas Tanjungpura, 2018)
This study aims to determine the chemical characteristics of peat soil in various depths of water drainage. This research was conducted in Rasau Jaya General Village Rasau Jaya Sub-district, Kubu Raya Regency. Soil analysis was conducted at Soil Chemistry and Soil Fertility Faculty of Agriculture, University of Tanjungpura Pontianak. Soil sampling is done by disturbed soil sampling method and done by diagonal. Soil sampling was conducted on 3 plot of land observation, consisting of P0 without drainage channel, P1 drainage water channel depth 30 cm and P2 water depth of drainage channel 60 cm. Each plot is 40 x 50 m in size and there are 5 observation points. Each observation point there are 2 depths of 0-20 cm and 20 - 40 cm. The method used is descriptive data analysis to see comparison of chemical characteristics of peat soil in each plot of land P0, P1, and P2 which contained some water depth of drainage channel. The parameters observed in this study were soil reaction (soil pH), cation exchange capacity (CEC), base saturation (KB), N-total (%), P available (ppm), K (cmol (+) ã€–kgã€— ^ (-1)), Ca (%), Mg (%), C-Organic (%). Keywords: Chemical Characteristics, Peat, Drainage.